Error estimate for optimality of distributed parameter control problems via duality. (1995) - Chan, W. L.; Yung, S. P.
Abstract : Sharp error estimates for optimality are established for a class of distributed parameter control problems that include elliptic, parabolic, hyperbolic systems with impulsive control and boundary control. The estimates are obtained by constructing manageable dual problems via the extremum principle.